Disorder and optical properties of amorphous carbon - Kopidakis, Georgios; Patsalas, Panos; Kelires, Pantelis C.; Mathioudakis, Christos (My University, 2007)
Tight-binding calculations shed light onto the link between disorder and optical properties in pure amorphous carbon films. It is shown that the Urbach energy EU is an excellent probe of disorder in such films. Our striking finding is that EU varies non-monotonically with sp3 fraction and optical gap, contrary to what is seen experimentally in hydrogenated samples. Firm evidence is provided, supported by experimental measurements, that in dense films the higher the sp3 fraction the lower the disorder. The Urbach energy has a value of 0.09 eV for the 100% sp3-bonded network, it reaches a maximum of 0.3 eV for 65% sp3 content, and it then declines to low values for low-sp3 content films. Analysis of cluster distributions and bond-angle and -length distortions reveals that the Urbach edge is associated to both topological and structural disorder. Another notable finding is that the edge is rather insensitive to the spin density due to unpaired sp2 sites.
Keywords: Amorphous carbon; Simulation; Pulsed laser deposition; Optical properties